Resistance Training of Inspiratory Muscles After Coronary Artery Disease May Improve Obstructive Sleep Apnea in Outpatient Cardiac Rehabilitation: RICAOS Study - Labeix, Pierre; Berger, Mathieu; Zellag, Amandine; Garcin, Arnauld; Barthelemy, Jean-Claude; Roche, Frederic; Hupin, David (Frontiers in Physiology, 2022)
Background:Obstructive sleep apnea (OSA) affects 5% of the adult population and its prevalence is up to 13 times higher in coronary artery disease (CAD) patients. However, OSA in this population is less symptomatic, leading to lower adherence to positive airway pressure (CPAP). While oropharyngeal exercise showed a significant decrease in apnea hypopnea index (AHI) in patients with moderate OSA, there have been no studies testing the impact of specific inspiratory muscle training (IMT) for these patients.The aim of our study was to assess the effectiveness of IMT on AHI reduction in CAD patients with moderate OSA. Methods:We included patients with CAD involved in a cardiac rehabilitation program and presenting an AHI between 15-30. Patients were randomized in a 1:1 allocation to a control group (CTL - classic training) or an IMT group (classic training + IMT). IMT consisted in 60 deep inspirations a day, 6 days a week, into a resistive load device set at 70% of the maximum inspiratory pressure (MIP). After 6 weeks, we compared AHI, neck circumference, Epworth Sleepiness Scale, Pittsburgh Sleep Quality index and quality of life with the 12-item Short Form Survey before and after rehabilitation. Results: We studied 45 patients (60±9 y; BMI=27±6 kg.m-2). The IMT group (n=23) significantly improved MIP (p<0.05) and had a significant decrease in AHI by 25% (-6.5 ± 9.5, p=0.02). In the CTL group (n=23), AHI decreased only by 3.5% (-0.7±13.1; p=0.29). Between groups, we found a significant improvement in MIP (p=0.003) and neck circumference (p=0.01) in favor of the IMT group. However, we did not find any significant improvement of AHI in the IMT group compared to CTL (p = 0.09). Conclusion: A specific IMT during cardiac rehabilitation contributes to reduce significantly AHI in CAD patients with moderate OSA. Magnitude of the decrease in OSA severity could be enhanced according to implementation of specific IMT in this population.